Principles of medical professionalism - Merlo, Gia (New York, NY : Oxford University Press, 2021)
'Principles of Medical Professionalism' will inform both future physicians and current practitioners that being a medical professional is not about being perfect, but rather about being human and recognizing our own limitations. The reader can therefore learn to manage their expectations about the profession while becoming more resilient to disruptions in the medical field such as artificial intelligence and the changing patient-doctor relationship. This book takes into consideration challenges to the uniform integration of a formal medical professionalism curriculum and addresses the critical need for support of practitioners' professional development and identity formation throughout the various stages and transitions in their medical career.
Also issued in print: 2021.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on March 17, 2021).
Keywords: Medicine -- Vocational guidance; Physicians -- Vocational guidance